A Journey to the Death: Book Review of "The Spaces In Between" by Carl Leggo and Kimberley Holmes - James, Kedrick (Art/Research International)

(untitled) (University of Alberta, 2022)
This book review explores the publication of an email correspondence between Carl Leggo and Kimberley Holmes which occurred over the period of time that Leggo was undergoing chemotherapy and radiation treatment for a brain tumour that eventually ended his life. It observes his role as a super-mentor of graduate students undertaking works in poetic inquiry and life writing, and his commitment to living poetically until his unfortunate passing in 2019. The review considers some ethical issues associated with this publication and the reasons why it provides useful insights to anyone committed to academic mentorship.